EU-Richtlinie Fauna-Flora-Habitat: Umsetzungsprobleme und Erklärungsansätze. - Chilla, Tobias (TH Zürich, ORL-Institut, 2005)
Der Beitrag ergänzt die bestehende Literatur zur Implementierung der FFH-Richtlinie in Deutschland um einen konstruktivistischen Ansatz, der interdisziplinär in einem Projekt am Geographischen Institut der Uni Köln bei der Untersuchung der Bedeutung von Institutionen und policy-Netzwerken am Beispiel der FFH-Richtlinie in NRW verfolgt wird. Gegenüber den traditionellen Erklärungsansätzen, die die Implementationsproblematik primär mittels institutioneller und "technischer" Aspekte des Politikprozesses betrachten, legt der Beitrag Wert auf die inhaltlichen Aspekte und deren Rezeption und Verhandlung durch die beteiligten Akteure, also eine diskursanalytische Herangehensweise. oc/difu

The Habitats Directive of the European Council was adopted in 1992 and aims to protect wild fauna and flora as well as to conserve their habitats on a transboundary European scale. Jointly with the areas of the 1979 Bird Protection Directive, the selected areas will make up the Natura 2000 Network, which is the most important outcome of the European biodiversity policy. The site selection process is now being brought to an end in most member states of the EU. In most countries, including Germany, the implementation was characterized by delays and conflicts, especially on the local and regional levels. This gives reason to analyze the process of implementation of this directive in retrospective. The article discusses the explanations of the respective literature (e.g., openness of the directive, its tight schedule, the practices of participation). Subsequently, the question is raised if explanations other than technical or institutional may contribute to the understanding of these space-related conflicts. Both nature and space are not only material entities, but also communicated, negotiated and thereby socially constructed categories. difu
Keywords: Natur; Umweltschutz; Umweltpolitik; Europarecht; Naturschutz; Tierwelt; Vegetation; Fauna-Flora-Habitat-Richtlinie; Implementation; Nichtregierungsorganisation; Biodiversität